Analysis of energy crops assortment in Ukraine - Syplyva, N.; Kulyk, М.; Rozhko, І.; Rytchenko, А. (Scientific Progress & Innovations, 2025)
The use of alternative energy sources is critically important for most countries today, which will help solve the problem of affordable and cheap energy and mitigate the effects of global warming. The main, most accessible and renewable raw material for energy production is plant biomass. Our task was to identify the most productive varieties of herbaceous and woody energy crops that would meet the needs of production. To accomplish this task, we conducted analytical research. In our work, we used the following methods: dialectical cognition of processes and phenomena, monographic; empirical; comparative analysis and abstract and logical approach. As a result of the analysis of the quantitative composition of the updated assortment of energy crops, it was determined that as of 2024, the assortment of these crops in the Register of Varieties includes 73 units, which include 35 varieties of woody and 38 herbaceous energy crops. Most of the varieties in the Register are from the Poaceae family. Over the past five years, the Register of Varieties has been updated with 34 varieties, including only seven herbaceous crops. The varieties are represented by such species as sugar sorghum – six varieties and two variety of giant miscanthus. The average yield of Salix varieties ranges from 32.0 to 39.0 t/ha of crude biomass with a fuel value of 16–19 MJ/kg. We also drew attention to the dynamics of breeding and seed production of energy crops. It should be noted that among the scientific institutions of Ukraine, the following institutions are engaged in seed production and selection of herbaceous energy crop varieties: M. M. Gryshko National Botanical Garden of the National Academy of Sciences of Ukraine, Institute of Bioenergy Crops and Sugar Beet of the National Academy of Agrarian Sciences of Ukraine, Breeding and Genetic Institute - National Center for Seed Science and Variety Studies, State Institution Institute of Cereals of the National Academy of Agrarian Sciences of Ukraine, etc. Taking into account the botanical and biological characteristics of the representatives of this group of energy crops and the potential of the declared productivity, the most productive varieties for each growing zone were identified in the characterization of plant varieties declared in the Register of Plant Varieties Suitable for Growing in Ukraine. In the future, this will allow to produce a sufficient amount of seed and planting material for the establishment of new highly productive areas of energy crops.